Evaluation of Phytochemical Content and the Antioxidant and Antiproliferative Potentials of Leaf Layers of Cabbage Subjected to Hot Air and Freeze-Drying - Do Manh Cuong; Hee Young Kim; Meran Keshawa Ediriweera; Somi Kim Cho (Journal of Food Quality)
Cabbage (Brassica oleracea var. capitata f. alba), a cruciferous vegetable, is one of the most widely consumed vegetables worldwide. However, research on whether there are differences in its contents of phytochemicals and biological activities according to the drying method for each portion of the vegetable remains insufficient. The present study investigated the contents of representative polyphenols and isothiocyanates, the antioxidant capacity, and the antiproliferative effects among six leaf layers of cabbage subjected to hot air and freeze-drying. High-performance liquid chromatography analysis showed that most phenolic and flavonoid bioactive compounds were significantly accumulated in the outer cabbage leaf layer (P1), whereas isothiocyanates were most abundant in the leaf layer close to the core of the head (P5). The contents of isothiocyanates, gallic acid, epicatechin, p-coumaric acid, sinapic acid, and myricetin were significantly higher in the hot air-dried sample than in the freeze-dried sample, whereas the contents of catechin hydrate, chlorogenic acid, 4-hydroxybenzoic acid, and rutin hydrate were significantly higher in the freeze-dried sample. Compared to other leaf layers, P1 exhibited high antiproliferative efficacy against pancreatic, breast, and gastric cancer cells. P1 also showed excellent DPPH·(EC 50–4.208 ± 0.033 and 4.611 ± 0.053 mg/mL for hot air and freeze-dried samples, respectively) and ABTS· (2.422 ± 0.068 and 2.224 ± 0.070 mg/mL for hot air and freeze-dried samples, respectively) radical-scavenging effects. These results indicate that the contents of polyphenols and isothiocyanates in cabbage may vary depending on the leaf layer and the drying method. Our findings provide insight for applying appropriate food drying methods that can be used to produce cabbage leaf-based products with enhanced bioactivity.